Building the Self Adaptation Scale for Students of the College of Physical Education and Sports Sciences at Tikrit University - Abed Al- Janabi, Saad Abbas; Amir Finjan, Raad Abdul; Ali Dwiger, Mehdi (International Journal of Psychosocial Rehabilitation, 2019)
The issue of youth is one of the important topics addressed by scientists in education, physical education and psychology their care and special attention because they prepare the wealth of the nation and its true stock and precious stock of human forces and human energies, and they are the most important element in the planning process for the future of any people aspiring to develop their lives and civilization. And a tremendous power to defend the nation and the dignity of the nation.